EFFICACY OF INTRAUTERINE INFUSION OF IMMUNOMODULATORS AND PGF2alpha IN THE TREATMENT OF ENDOMETRITIS IN BUFFALOES - RAJU, K G SOLMON; NAIDU, K VENUGOPAL; RAO, K SADASIVA (The Indian Journal of Animal Reproduction, 2023)
A total of 72 buffaloes suffering from endometritis were utilized for the study. The affected buffaloes 12 each were treated with PBS, Lipopolysaccharides (LPS), Lysozyme (LZ), Oyster glycogen (OG), Vit. E and Selenium (SE); and PGF 2alpha (PG) Vm. Higher percentage of buffaloes suffering from endometritis was recovered with LPS (83.33), LZ (75.00), OG (66.67) and PGF 2alpha (66.67) than the SE (50.00) and control PBS ( 16.67). The conception rates were 53.33, 41.67, 33.33, 50.00, 25.00 and 16.67 In buffaloes treated with LPS, LZ, OG, SE, PG and untreated (PBS) groups, respectively. The bacterial colony counts were 79.58± 8.10, 77.92 ± 5.15, 89.67 ± 5.05, 73.67 ± 7.33, 83.50 ± 6.19 and 70.86± 5.14 before treatment in PBS, LPS, LZ, OG, SE and PG groups of buffaloes, respectively while the same after treatment were 126.83 ± 8.27; 6.67 ±1.39, 12.87 ± 3.35; 21.00 ± 5.93; 27.75 ± 4.10 and 24.75 ± 5.38, respectively. The progesterone (P4) profiles were 1.07±0.24; 0.81±0.10; 1.07:i:0.18; 1.03:t 0.19; 0.98 ± 0.14 and 1.09 ± 0.14 ng /ml before treatment and 1.13±0.22; 0.32 :i: 0.03; 0.37 :i: 0.05; 0.48 ± 0.07; 0.48 ± 0.08 and 0.40 ± 0.05 ng /ml after treatment in PBS control, LPS, LZ, OG, SE and PG groups, respectively.